Odpowiedzi

2010-02-23T12:34:32+01:00
A)9*(-5)+1/64=-45+1/64=-44 63/64
b)pier z 2*13/3* - 25/3=pir z 2 * -325/3= -325 pier z 2/3
c)-16+16/9 - 8/125=-16+ 2000/1125-1000/1125=-16+1000/1125=-15 125/1125
d) [5-3×(⅖)⁰]⁻² = [5-3×1]⁻² = [5-3]⁻² = 2⁻² = (1/2)² =1/4
Najlepsza Odpowiedź!
2010-02-23T12:40:47+01:00
27⁻⁵/₃+ (¹/₁₆ ) ¼ = (¹/₂₇) do potęgi ⁵/₃ + ⁴√¹/₁₆ = ∛[(⅓)³]⁵ + ½ =
=(⅓)⁵ + ½ = ¹/₂₄₃ + ½ = ²/₄₈₆ + ²⁴³/₄₈₆ = ²⁴⁴/₄₈₆ = ¹²²/₂₄₃

b)√2 ×4 ⅓×8 ⁻⅓ =√2 × ¹³/₃ × (⅛) do potęgi ⅓ = √2 × ¹³/₃ × ∛⅛ = √2 × ¹³/₃ × ½ = √2 × ¹³/₆ = 2½ √2

c)2 ⁻⁴+ (⁴/₃)⁻² + (⅖)⁻³ = (½)⁴ + (¾)² + (⁵/₂)³ = ¹/₁₆ + ⁹/₁₆ + ¹²⁵/₈ =
¹/₁₆ + ⁹/₁₆ + ²⁵⁰/₁₆ = ²⁶⁰/₁₆ = ⁶⁵/₄ = 16 ¼

d) [5-3×(⅖)⁰]⁻² = [5-3×1]⁻² = [5-3]⁻² = 2⁻² = (½)² = ¼